El ciclo de vida y el manejo del cacaotal - Somarriba, Eduardo; Cerda Bustillos, Rolando; Quesada Chaverri, Francisco; Astorga Domian, Carlos; Orozco Aguilar, Luis; Villalobos Rodríguez, Marilyn; Orozco Estrada, Shirley; Corrales Mora, Alexander; Villegas Cáceres, Romina; Say Chávez, Eduardo; Deheuvels, Olivier (2015)
CATIE (Centro Agronómico Tropical de Investigación y Enseñanza)